Konsep Animalia Menggunakan Model Kooperatif Berbasis Inkuiri - Indriyani, Sari (Journal of Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2014)
The learning process is expected by the government has not fully implemented at SMAN 2 Banjarbaru.Students could more only focus on the cognitive aspects of development so the learning process did not run effectively and efficiently.This study aimed to: describe the activities of teachers in learning management; describe the activities of students in the learning process; determine the ability of partner's teachers in using learning instruments; measure the learning outcomes of students' products and processes; measure higher order thinking skills of students; describe psychomotor of students; describe affective student; describe the response of students and teachers towards learning. This study is  a Research of Development. (Research and Development / R & D). It was adopted from development model of Dick & Carey.Subject of this researh consisted of  5 people to test try out at small groups and 26 people for the class try out. They are students of SMAN 2 Banjarbaru class X school year 2012/2013.Data were collected and analyzed using descriptive analysis techniques. The result of this study is a prototype of learning instruments. Its material is about Animalia kingdom and using cooperative learning model and the type of inquiry-based learning together. Teachers did not dominate during learning activities held.Students did activities during the learning.The ability of model's teacher in using learning instruments was quite well with the average value of 3,51.Result oflearning product has showed 80,77% of students have reached the KKM.Result of learning process has showed 88,46% of students have reached the KKM. Students' higher-order thinking skills were 34,62% good, and 65,38% good enough. Psychomotor ability of students was categorized as good with average score of 99-100.Student's affective were observed from social skills in making questions, which was categorized as good. It was also observed from the characteristic behavior of cooperation and respect the opinion, which was categorized as good.Students' response to the learning activities of the cooperative model and the type of inquiry-based learning together is positive.